Great Ideas: Listeng and speaking activies for students of American English. Teacher Manual - Jones, Leo (New York: Cambridge University Press, 1987)
I You and me II Stranger than fiction III Can i help you? IV What a nice day?
Keywords: Inglés - Lengua